Knowledge Management and Family Business Continuity: The Moderating Effect of Length of Time in Existence (Global Journal of Management and Business Research, 2019)
Cases of family business failures are evident in Nigeria and particularly Lagos state, despite the array of studies attributable to such area. In addition, ownership dilution; transfer of both leadership and ownership tend to be seen as a phase in the company's life cycle, which form a part of managing continuity but less practiced by SMEs' owner/managers. Family businesses in Lagos State are seen to have large failure rate, or struggle to survive after a long time. One of the major issue to which this can be attributed to is the rarity in proper knowledge management practice and heritage struggle due to lack of or poor succession planning. The broad objective of the study was to establish the influence of length of time in existence on the relationship between knowledge management and family business continuity. The population of interest was all family businesses operating in selected Local Government Area of Lagos State Nigeria. The study employed a survey research design. Data was collected from the owners, family members, partners, management, spouses, relatives and management workers of small and medium scale enterprises (SMEs) using questionnaires.
Keywords: knowledge management; family business continuity; length of time in existence; SMES; lagos state